Trastuzumab emtansine (T-DM1) and concurrent radiotherapy for treatment of HER2-positive breast cancer: Review of literature. Issue 5 (2021) - Muto, M; Amaturo, G; Sgambato, A; Colantuoni, G; Iannace, C; Gridelli, C
No abstract available